The factors contributing to the abandonment of residential projects in Alor Setar, Kedah - Ibrahim, Nur Irdina (2025)
The issue of abandoned residential projects remains a significant challenge in Malaysia’s property development sector, particularly in Alor Setar, Kedah. This study aims to investigate the crucial factors that contribute to the abandonment of residential projects in Alor Setar, Kedah and embarks on these objectives, identify the factors that contribute to the abandonment of residential projects and suggest the best solution in mitigating the abandonment of residential projects. A quantitative research method was implemented, with data collected through questionnaires that distributed to registered developers in the Alor Setar region. Analysis using the Statistical Package for Social Sciences (SPSS) discovered that financial constraints, fluctuating construction material costs, poor project management, and limited buyer affordability were among the most influential factors. Additionally, delays in government approvals and weak market demand were also noted as major contributors. The findings suggest that enhancing regulatory enforcement, improving financial planning, and revising development policies could help reduce project abandonment. The study contributes valuable understandings for developers, policymakers, and industry stakeholders to develop more resilient and sustainable residential projects.